Utilization of Molecular Systems for the Identification and Typing of Clinically Relevant Multiple Drug Resistant Staphylococcus Aureus - Neela, Vasantha Kumari (2005)
Staphylococcus aureus is an important human nosocomial pathogen that can cause a variety of skin infections and toxin-mediated diseases including gastroenteritis, staphylococcal scalded-skin syndrome and toxic shock syndrome. Whilst the use of antibiotics can kill most strains of pathogenic microbes, the increase of multiple drug resistant S. aureus, especially among hospital patients have been a worrying trend. In order to treat patients infected with this organism at the earliest time possible and to prevent further nosocomial outbreaks, it is necessary to rapidly identify the multiple drug resistant S. aureus, so that the patient can be treated with the correct antibiotic on time and thus prevent further complications. S. aureus besides being a nosocomial pathogen causing frequent nosocomial infections also causes community acquired outbreaks. The increased prevalence of S. aureus infections may be prevented if the epidemiology of S. aureus is studied, whereby the spread of outbreak clones can be identified and treated with the appropriate drugs. Therefore, the aim of this study was to investigate suitable molecular systems for use in the rapid identification ofS. aureus and detection of multiple drug resistant S. aureus and for typing of strain variations for epidemiological understanding ofS. aureus in Malaysia. In this study, a total of eighty-nine clinical S. aureus isolates obtained from five different hospitals in Malaysia and from one pathology laboratory were studied. All the isolates were confirmed for S. aureus by the presence of species-specific Sa442 fragment (s. aureus specific fragment). Sequencing of the Sa442 fragment from isolates obtained from the different geographical locations identified this fragment as an epidemiological marker as it showed a wide variation of 1-10 % in the nucleotide sequences among the S. aureus isolates studied. For rapid identification of S. aureus and detection of multiple drug resistant strains, two molecular assays were utilized. In the first assay, a multiplex peR based strategy was used, whereby the genes responsible for methicillin (mecA), mupirocin (ites2), gentamycin (aac(6')-aph(2")), erythromycin(ermA) resistance and species specific Sa442 fragment were amplified. Results of the assay indicated the amplification of antibiotic resistant genes and Sa442 fragment at the expected sizes of 533,456, 174, 139 and 108bp respectively. All the amplified products were further confirmed by sequencing. The second assay was a membrane assay based on an optimized dot blot hybridization technique. In the dot blot assay, a set of oligonuclotide probes designed from the antibiotic resistance genes and the Sa442 fragment sequences were highly sensitive and specific for the respective bacterial target genes. The membrane assay developed was able to detect multiple drug resistant S. aureus isolates in less than two hours after obtaining pure culture isolates. Detection is also possible in less than two hours from spiked urine and blood samples, as well as for direct nasal samples. The results obtained with both polymerase chain reaction (PCR) and membrane assay were found to be similar whereby, 58.8, 67.7, 97.7 and 1.1% of the isolates carried mecA, aac(6')-aph(2"), ermA and iles-2 genes respectively. The overall correlation between the antibiotic resistance (disc diffusion test) and presence of antibiotic resistant genes (PCR and membrane assay) were found to be 77.3% for methicillin, 73.7 % for gentamycin, 95.4% for erythromycin and 100% mupirocin. The molecular epidemiology of local S. aureus was studied using randomly amplified polymerase chain reaction (RAPD) and repetitive element sequence based PCR (repPCR). Four out of the 20 arbitrary primers screened were highly efficient for use in molecular typing of S. aureus isolates. The rep-PCR typing primers designed from the staphylococcal repetitive sequences (STAR) were also markedly feasible for typing of S. aureus isolates. The RAPD study for molecular epidemiology showed wide variation in S. aureus isolates, as seen by genetic distance value based on Jaccard's index ranged from 0.037 to 0.954545. Similarly, in rep-PCR study, a wide variation in genetic distance value based on Jaccard's index ranged from 0.037037 to 0.894737. A wide variation in genetic distance was seen in the clonal diversity of local S. aureus isolates, where by, isolates were divided into four (4) clones namely Miri, Kuantan, Kota Bharu and Seremban, with Miri as the most predominant clone. In addition, RAPD was able to distinguish between methicillin resistant Staphylococcus aureus (MRSA) and non-MRSA isolates, showing the spread of two MRSA clones in Malaysia. RAPD analysis produced two (2) molecular markers, at positions 500 bp with primer OPAE 14 and 750 bp with OPAE 15, whereas, rep-PeR produced three (3) molecular markers, positions 500 with rep primer!, between 1500 and 2000 bp with rep 2, and slightly above 750 bp with rep primer 3, in most of the S. aureus isolates studied. From the five (5) markers obtained with RAPD and rep-PCR, the putative 500 bp rep marker was cloned in PCR 2.1 Topo vector and sequenced. The 500 bp rep marker was selected, as this marker was obtained through the amplification of S. aureus isolates with the primer designed from S. aureus genome and also because of the small size. The sequence obtained identified the repmarker as a 489 bp fragment, showing 95% homology to a region in glyceraldehydes -3phosphate dehydrogenase (GAP) operon in S. aureus genome, whose coding potential is unknown. The higher percentage (95%) similarity of the rep marker to S. aureus genome emphasized the importance of the rep marker in species-specific identification. To investigate the potentiality of the rep marker in species-specific identification of S. aureus isolates, a PCR and a membrane assay were developed with primers and probe designed from the rep sequence. The PCR and membrane assay showed positive signal for all eighty-nine S. aureus isolates tested and no signal was seen for other Grampositive and Gram-negative species tested, appreciating the specificity and the sensitivity of rep primers and probes in species-specific detection of S. aureus isolates. Sequencing of the rep marker from isolates obtained from different geographical locations, identified this marker (rep) as a potential diagnostic marker as it is highly conserved in S. aureu genome showing 98-99% sequence similarity among the isolates. Besides for diagnosis, using two typing procedures (RAPD and rep-peR) to study the clonal relatedness among the local S. aureus isolates which were developed with suitable RAPD and rep primers, they were able to correctly type S. aureus isolates according to the geographical location and also to differentiate between MRSA and non-MRSA. Although the RAPD primers are commercially available, the rep primers identified are still not published for use in typing S. aureus. The patterning of the novel rep primers and probe for typing and diagnosis of S. aureus will be extremely useful in the clinical diagnosis as the primers and probes innovated are highly specific and ubiquitous in all S. aureus isolates. These novel achievements made in the study will be of great value in the modern diagnostic era as the molecular systems optimized could be readily applied in the clinical diagnosis due to the specificity and rapidity in the detection of multiple drug resistant S. aureus. The achievements of the current study is especially a significant contribution to the clinical diagnostics and infectious disease research because the utilization of the optimized system incorporated as diagnostic kit will enhance the sensitivity and rapidity of molecular based detection in combination with sub-typing ability. Therefore, the routine application of the molecular systems optimized and the primers and probes developed in this study for the rapid identification of multiple drug resistant S. aureus and to study the epidemiology of S. aureus will definitely contribute towards early diagnosis of S. aureus infection in clinical laboratories. The epidemiological investigation will aid in developing more effective strategies in preventing and controlling the further spread of multiple drug resistant S. aureus clones in Malaysia